(untitled) (Journal of Geography and Environmental Management, 2018)
To the article the estimation of ecological situation of region of Southern Aral Sea Area is driven, and also the results of cross-correlation analysis are presented between the levels of some parameters of composition of drinking-water and atmospheric air with general morbidity of adult and child’s population of Karakalpakstan. The linear trend shows a decrease in the proportion of specific weight of non-standard samples of tap water by chemical indices. The linear trend of indicators of non-standard samples of tap water in terms of bacteriological indicators shows a certain stability of the indicators of pollutants.